Usage of biological chitosan against the contamination of post-harvest treatment of strawberries by Aspergillus niger - El-araby, Abir; El Ghadraoui, Lahsen; Errachidi, Faouzi (Frontiers in Sustainable Food Systems, 2022)
Developing bioactive food packaging capable of extending fruits shelf life has received increasing attention in recent years. The present study highlights the interest of strawberries post-harvest treatment with chitosan as a preservation solution. It extraction was carried out from shrimp shells chitin (Parapenaeus longirostris) using citric acid during demineralization step. Produced chitosan was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Amino group (-NH2) presence in obtained chitosan was confirmed by infrared (IR) spectral data. Deacetylation degree (DD), which has a value of 80.86%, was determined from FTIR spectra. X-ray diffraction pattern (XRD) showed two peaks of crystalline character, characteristic of extracted chitosan, approximately at 20º and 30º (2θ). Produced chitosan morphology is characterized by a relatively smooth upper surface and fibrous structures observed from SEM analysis. Chitosan, acetic acid, and their interaction effects were evaluated on mycelial fungus growth of Aspergillus niger strain isolated from spoiled strawberry fruits. Chitosan revealed a strong antifungal activity, dose-dependent (from 0 to 3%), on Aspergillus niger mycelial growth while acetic acid showed moderate antifungal activity. Agri-food application was carried out using chitosan solubilized in acetic acid as a post-harvest treatment tool for strawberries shelf life prolongation (by using an experimental design). Coating, with the developed preservative solution, significantly reduced microbial spoilage in strawberry fruits. Treated strawberries retained their initial pigmentation for a longer period when compared to untreated strawberries. The treatment carried out maintained treated strawberries cellular structures during storage period. Applied treatment extended fruits shelf life which is considered very susceptible to reduce post-harvest losses.